A frustrated alternative to the Spanish commercial monopoly with America: the privileged Company for Universal Trade with the Indies of 1738 - Manuel BUSTOS RODRÍGUEZ (Studia Historica: Historia Moderna, 2020)
One of the key instruments in the commercial and financial order to understand the economic globalization of the Early Modern Age as a result of overseas expansion is undoubtedly that of the privileged trading companies. These develop in Europe, basically, from the creation in England and Holland, at the beginning of the 17th century, of those referring to the West and East Indies. In Spain, as in other countries, they would develop later, after different frustrated attempts. In this country, an ambitious project by an unknown author will arise in 1738 to create the «Royal Company of the West Indies» to replace the existing ones and the commercial institutions that control the Carrera de Indias. This article studies in detail its content (managers, organization, financing, budget, profit forecast, access to the slave trade, privileges, etc.), as well as the reports issued by the experts consulted in this regard, until reaching his final rejection.